The overview of the psychological techniques used in REBT and CBT - Bozhok, Natalia (My University, 2016)
In the article the principles of the rational emotive behavioral therapy (REBT) and cognitive behavioral therapy (CBT) are studied. This paper presents the theoretical analysis of the psychological techniques and the peculiarities of their use on the basis of REBT and CBT. It also defines the way how to apply the mentioned interventions to effect positively the person’s psychological health and well-being. The paper also outlines the importance of combining cognitive, emotive and behavioral interventions and shows their contribution in developing person’s rational thinking and control of emotions and constructive behavior.
Keywords: емотивно-біхевіористична терапія; когнітивно-поведінкова терапія; нераціональні думки; раціональні думки; раціональне мислення; ABC-аналіз; психологічні техніки; особистість; рациональная эмотивно-бихевиористическая терапия; когнитивно-поведенческая терапия; нерациональные мысли; рациональные мысли; рациональное мышление; психологические техники; личность; rational emotive behavioral therapy; cognitive behavioral therapy; irrational beliefs; rational beliefs; rational thinking; ABC analysis; psychological techniques; individual; кафедра ділової іноземної мови та міжнародної комунікації